PENGARUH MODEL PEMBELAJARAN PBL BERBANTUAN VIDEO ANIMASI TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV SDN 067776 MEDAN JOHOR - Ayu Afsarini; Yusra Nasution; Nurhairani; Fahrur Rozi; Husna Parluhutan Tambunan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research was motivated by the low science learning outcomes of fourth-grade students at SDN 067776 Medan Johor, caused by the conventional, teacher-centered learning process. This study aimed to determine the effect of implementing the Problem-Based Learning (PBL) model assisted by animated videos on the science learning outcomes of fourth-grade students at SDN 067776 Medan Johor. This study used a quantitative research method with a Quasi-Experimental research design with a Nonequivalent Control Group Design. The sample consisted of two groups: 20 fourth-grade students as the control class and 20 fourth-grade students as the experimental class. Data collection techniques used were multiple-choice tests and documentation. The data analysis techniques used were normality, homogeneity, and hypothesis testing, processed using SPSS 31. The results showed a significant difference in the average post-test scores between the experimental and control classes. Based on the statistical test, a significance value (2-tailed) of 0.000 < 0.05 was obtained, thus H1 was accepted and H0 was rejected. It can be concluded that the Problem-Based Learning (PBL) learning model assisted by animated videos has an effect on the science learning outcomes of fourth-grade students at SDN 067776 Medan Johor.